1998
DOI: 10.1073/pnas.95.5.2238
|View full text |Cite
|
Sign up to set email alerts
|

A poly(A) binding protein functions in the chloroplast as a message-specific translation factor

Abstract: High-affinity binding of a set of proteins with specificity for the 5 untranslated region (UTR) of the Chlamydomonas reinhardtii chloroplast psbA mRNA correlates with light-regulated translational activation of this message. We have isolated a cDNA encoding the main psbA RNA binding protein, RB47, and identified this protein as a member of the poly(A) binding protein family. Poly(A) binding proteins are a family of eukaryotic, cytoplasmic proteins thought to bind poly(A) tails of mRNAs and play a role in trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
84
1
1

Year Published

2000
2000
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 55 publications
1
84
1
1
Order By: Relevance
“…The m/z peak of 1774. 25 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The data support N-acetylation, because the unmodified N-terminal peptide (m/z 1732.49) could be generated by acid-catalyzed deblocking (28) when the enzymic reaction was stopped with 1% trifluoroacetic acid.…”
Section: Fig 2 Separation Of Spinach 30 S Prps By Reversed-phase Hpmentioning
confidence: 74%
See 1 more Smart Citation
“…The m/z peak of 1774. 25 [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. The data support N-acetylation, because the unmodified N-terminal peptide (m/z 1732.49) could be generated by acid-catalyzed deblocking (28) when the enzymic reaction was stopped with 1% trifluoroacetic acid.…”
Section: Fig 2 Separation Of Spinach 30 S Prps By Reversed-phase Hpmentioning
confidence: 74%
“…Plastid mRNA is edited in most plants, and the mature mRNA levels remain relatively unchanged through dark/light transitions, whereas protein synthesis rates increase dramatically upon illumination (8,9). Nuclear-encoded factors mediate light-regulated translation (10) as well as transcription and post-transcriptional processes in plastids (11,12), and many isolated nuclear mutants interfere with polysome assembly (13). Thus, unlike in E. coli or cyanobacteria, the plastid translation system functions with additional regulatory elements under the control of the nuclear genome.…”
mentioning
confidence: 99%
“…Among these, only RB47 directly contacts the RNA, as was determined by UV-crosslinking assays. The genes for both RB47 and RB60 were cloned and shown to encode a poly(A)-binding protein (cPABP) and a protein disulfide isomerase (cPDI), respectively (Kim and Mayfield 1997;Yohn et al 1998). The binding activity of this complex was decreased in nuclear mutants, which affected D1 synthesis, underlining its function for translation initiation.…”
Section: Rbps Interacting With 5¢utrsmentioning
confidence: 99%
“…3), it is possible that RB47 may bind both UTRs of psbA mRNA when they are present in cis. This may not be entirely surprising as the 3Ј-UTR is AU-rich, and RB47 shares high homology with poly(A)-binding proteins (31). In this scheme, the simultaneous binding of RB47 and its associated proteins to the 5Ј-and 3Ј-UTRs forms a high affinity complex (Fig.…”
Section: Fig 4 Specificity Of Binding Of 5-utr and 53-tmentioning
confidence: 99%
“…The UVCL assay, which labels proteins that are in direct contact with the RNA, showed that RB47 is the primary RNA-binding protein of the complex (Fig. 3 and Ref. 3), and cloning of RB47 showed that it contains RNA-binding domains (31). Extraction of the proteins that were complexed with the 5Ј-UTR of psbA mRNA in the GMS assay revealed that RB60 is also associated with the RNA, potentially via protein-protein interactions with RB47 (3).…”
Section: Fig 4 Specificity Of Binding Of 5-utr and 53-tmentioning
confidence: 99%